Pembangunan Kerohanian Usahawan Melayu di Malaysia : Tinjauan dari Perspektif Guru-Guru Murshid - Ahmad Fakhrurrazi Bin Mohammed Zabidi; Abu Yazid Bin Abdul Kadir; Salmy Edawati Binti Yaacob (USIM Press, 2024)
VOL. 27 (2022) Page (158-175)